Furoshiki and the Japanese art of gift wrapping - Kakita, Tomoko (Laurence King Publishing, 2021)
"Perfect the gift of giving. The only modern, practical guide to the ancient art of Japanese gift wrapping. Make gift-giving extra special (and help save the planet) with 30 exquisite yet easy styles. In Japan, gift giving is an important cultural ritual, and the presentation is just as important as the gift itself. Discover a variety of wrapping styles, involving knotted or intricately folded furoshiki or tsutsumi cloth. With no cutting, sticking or waste your furoshiki is completely reusable. As well as gifts you can also use furoshiki to wrap and carry all sorts of items. Say goodbye to wrapping paper and plastic shopping bags for good." --